Thor, Ragnarok [videorecording (Blu-Ray + DVD)] - Pearson, Eric, 1980-; Kyle, Craig; Yost, Christopher; Hemsworth, Chris; Hiddleston, Tom; Blanchett, Cate, 1969-; Elba, Idris; Goldblum, Jeff, 1952-; Thompson, Tessa, 1983-; Urban, Karl, 1972-; Ruffalo, Mark; Hopkins, Anthony, 1937-; et al. (Marvel Studios, 2018)
Thor is imprisoned on the other side of the universe and finds himself in a race against time to get back to Asgard to stop Ragnarok, the destruction of his home world and the end of Asgardian civilization, at the hands of an all-powerful new threat, the ruthless Hela.